Effectiveness of problem-based learning on low achievers' academic achievement in the ESL classroom - Abu Bakar, Noor Idayu; Noordin, Nooreen (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
This paper proposes a study on the implementation of Problem-based learning (PBL), using Cooperative Problem-Based Learning model, to determine its effectiveness on academic achievement of the low-achieving English language learners at tertiary level in a technical institution in Malaysia. The study will primarily employ a quasi-experimental design with non-randomised (pre-test and post-test) control group. It will involve thirty-two students purposely selected from certificate programmes in the studied setting. Instruments which will be used in this study are a comprehensive achievement test, a retention test and a questionnaire. Besides that, an inclusion of qualitative data in the study from self-reports and field notes attempts to seek better understanding of the factors facilitating or impeding students’ learning during the implementation of PBL.